The politics of space: Vietnam as a Communist heterotopia in Viet Thanh Nguyen’s The Refugees - Asl, Moussa Pourya (Penerbit Universiti Kebangsaan Malaysia, 2020)
Viet Thanh Nguyen’s The Refugees (2017) explores hardships and aspirations of non-Communist Vietnamese led between two contradicting geographical imaginations. This article draws upon Foucault’s theories of “other spaces”—heterotopia, utopia and dystopia—to examine the socio-political constructs of space in the manufacturing and diffusion of desired knowledge(s) throughout the collection. It is argued that the particular arrangement of spaces together with the strategic monopolization of knowledge-producing practices throughout the stories produce the effects of regulatory and disciplinary power with the aim of naturalizing certain discursive-ideological policies. The analyses of selected stories unravel the ways in which the Communist Vietnam is ideologically signed as a heterotopia, or a rupture of a decent society. The study also reveals that such negative depictions of the country are in compliance with mainstream epistemic perspectives in the West that aim to maintain a similar discursive regime. Hence, it is concluded that the juxtaposition of two irreconcilable spaces—the heterotopic representation of Vietnam in relation to the utopianised picture of America—feeds into the contemporary discourse of war on terror by reflecting the Cold War register of anxiety about an insidious Communist threat.